Parent–Child Agreement on Fatigue in Pediatric Otolaryngology Patients - Amy E. Ensing; Amy L. Zhang; Rebecca Z. Lin; Emma K. Landes; Henok Getahun; Judith E. C. Lieu (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objectives To investigate parent–child agreement on fatigue reporting in pediatric otolaryngology patients and whether agreement might vary by diagnosis and other patient factors. Study Design Cross‐sectional survey. Methods Patients ages 5–18 years old being evaluated for hearing loss (HL) or obstructive sleep apnea (OSA) were recruited from a pediatric otolaryngology clinic and sleep center. Children and parents completed the Pediatric Quality of Life Inventory Multidimensional Fatigue Scale (PedsQL MFS). Results Responses of 42 patients with HL, 49 with OSA, 10 with sleep‐disordered breathing (SDB), and 34 controls were analyzed. Parent and child PedsQL MFS scores were strongly correlated (Pearson r > 0.7) across groups with few exceptions. Only the median child–parent score differences for general domain score in the SDB group (12.5; 95% CI 2.08 to 22.9), and total score (7.41; 95% CI −0.69 to 25.7) and general domain score (11.5; 95% CI 2.08 to 27.1) in the developmental delay group met clinical significance thresholds. Wide confidence intervals prevented definitive conclusions regarding clinical significance. A pattern of decreased parent–child score correlations was observed in children reported to have delays. Weak (±0.1 to ±0.4) to moderate (±0.4 to ±0.69) correlations were observed for total score, general domain score, and cognitive domain score for children with reported developmental/speech/language delay. Conclusion Overall, the parent‐proxy PedsQL MFS demonstrates strong agreement with self‐reports for pediatric otolaryngology patients being evaluated for HL and OSA. However, parent–child score discrepancies within specific patient groups, especially children whose parents reported speech/developmental/language delays, emphasize the importance of administering self‐reports when possible. Level of Evidence 3